Influence of Slow-Paced Breathing on Inhibition After Physical Exertion - Laborde, Sylvain; Lentes, Theresa; Hosang, Thomas J.; Borges, Uirassu; Mosley, Emma; Dosseville, Fabrice (Frontiers in Psychology, 2019)
This research aims to investigate whether slow-paced breathing (SPB) improves adaptation to psychological stress, and specifically inhibition, when it is performed before or after physical exertion (PE). According to the resonance model, SPB is expected to increase cardiac vagal activity (CVA). Further, according to the neurovisceral integration model, CVA is positively linked to executive cognitive performance, and would thus play a role in the adaptation to psychological stress. We hypothesized that SPB, in comparison to a control condition, will induce a better adaptation to psychological stress, measured via better inhibitory performance. Two within-subject experiments were conducted with athletes: in the first experiment (N = 60) SPB (or control – neutral TV documentary) was realized before PE (“relax before PE”), and in the second experiment (N = 60) SPB (or the watching TV control) was realized after PE (“relax after PE”). PE consisted of 5min Burpees, a physical exercise involving the whole body. In both experiments the adaptation to psychological stress was investigated with a Stroop task, a measure of inhibition, which followed PE. Perceived stress increased during PE (partial η2 = .63) and during the Stroop task (partial η2 = .08), and decreased during relaxation (partial η2 = .15), however no effect of condition was found. At the physiological level PE significantly increased HR, RF, and decreased CVA (operationalized in this research via the root mean square of successive differences, RMSSD) in both experiments. Further, the number of errors in the incongruent category (Stroop interference accuracy) was found to be lower in the SPB condition in comparison to the control condition, however these results were not mediated by RMSSD. Additionally, the Stroop interference (reaction times) was found to be lower overall in “relax before PE”, however no effect was found regarding SPB and Stroop interference (reaction times). Overall, our results suggest that SPB realized before or after PE has a positive effect regarding adaptation to psychological stress and specifically inhibition, however the underlying mechanisms require further investigation.